The Importance Of Entrepreneurial Competencies On The Performance Of Women Entrepreneurs In South Africa - Zizile, Tola; Tendai, Chimucheka (Journal of Applied Business Research, 2018)
The study investigated the importance of entrepreneurial competencies on the performance of women entrepreneurs in East London, South Africa. The objectives of this study were to identify key entrepreneurial competencies that influence the performance of women entrepreneurs, to establish a relationship between entrepreneurial competencies and the performance of women entrepreneurs and to suggest strategies that can be implemented to improve entrepreneurial competencies of women entrepreneurs. Both primary and secondary data source were used in this research. This research followed a quantitative research design. A self-administered questionnaire was used to collect primary data. The findings of this research showed that entrepreneurial competencies are crucial for the survival and performance of SMMEs.
Keywords: Performance; Entrepreneurial; Competencies; SMME; South Africa